36=3(4-x)

Simple and best practice solution for 36=3(4-x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=3(4-x) equation:


Simplifying
36 = 3(4 + -1x)
36 = (4 * 3 + -1x * 3)
36 = (12 + -3x)

Solving
36 = 12 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
36 + 3x = 12 + -3x + 3x

Combine like terms: -3x + 3x = 0
36 + 3x = 12 + 0
36 + 3x = 12

Add '-36' to each side of the equation.
36 + -36 + 3x = 12 + -36

Combine like terms: 36 + -36 = 0
0 + 3x = 12 + -36
3x = 12 + -36

Combine like terms: 12 + -36 = -24
3x = -24

Divide each side by '3'.
x = -8

Simplifying
x = -8

See similar equations:

| 5x+x=8x+55+9x | | 25x-3=35x+5 | | 2p^3*6p^4= | | 20*.15= | | 8y-7-6y+2=0 | | 3x+27=20x-43 | | x/9+4=13 | | -9(x-4)+5x=-4(x+8)+5 | | 9*19+9= | | 2(4x+9)=-42+36 | | -x^2+8x-52=0 | | 12=4r-8+6r | | 4x-1(60-x)=130 | | 12/3x2/8 | | 1/2y-8=-7 | | 2+x=94 | | 7(y+9)+y=2(y+5)+4 | | 3x^2-12x-38=0 | | (12+8x)+13= | | 2x+5=7-2x | | 4th=60+10t | | 9x-5+3x+2= | | 3x^3-7x+6x-14=0 | | 0.3x=0.51 | | -3(2t-3)+2t=7t-3 | | 3xy+5x-2y+4yx+11x-8= | | -6z+4z=6z-8+7z | | 5x+2=-3+3x+17 | | (56/x-2)=x-3 | | (2/3)(x)+(1/2)(x-4)=x-4 | | 2y^2-15y-12=0 | | -22=-w-3 |

Equations solver categories